Hölderlin Heideggera: cezura i chiazm - Arne Melberg (Przestrzenie Teorii, 2009)
Katarzyna Szewczyk-Haake's translation of Arne Melberg's Heideggers Hölderlin, part of Några vändningar hos Hölderlin, Stockholm 1995.